OPTIMIZATION OF PROCESS PARAMETERS IN 3D PRINTING FDM BY USING THE TAGUCHI AND GREY RELATIONAL ANALYSIS METHODS - Arifin, Fatahul; Zamheri, Ahmad; Herlambang, Yusuf Dewantoro; Syahputra, Angga Panjy; Apriansyah, Icvan; Franando, Franando (Universitas Muhammadiyah Jakarta, 2021)
The 3D printing technology is one of the technologies that is developing currently. This machine can make products easily, quickly, and precisely. 3D printing is used to print models, prototypes/modeling, teaching aids for education, health support devices, product design, and many more in 3D shapes. Fused Deposition Modeling (FDM) is the most popular among others 3D printing techniques. In simple concept, it does not need maintenance regarding solvents or glue. The spare parts can be found easily and cheaply. In this research, we create objects by using Autodesk inventor that is called human denture. Then, it converted to G-Code using Simplyfy3D software version 4.1.2. The G-Code data is used in the 3D printer for making the product. We select parameters to print the product. In this study, we find the optimal parameters of the effect of shrinkage and hardness of the product. The 3 parameters are in this study namely; layer height, print speed, temperature print. The material of human denture is filament PLA +. The Taguchi method and Grey analysis are used to analyze the data result. The results of the analysis for optimal parameters are at Layer Height 0.15 mm, Print Speed 25 mm/s, and Print Temperature 210⁰C.